PENGARUH INVESTASI PARIWISATA TERHADAP PERUBAHAN STRUKTUR MATA PENCAHARIAN MASYARAKAT DESA DI SEKITAR NUSA DUA - I Made Sujana; Ni Luh Wulani Parwati; Anak Agung Istri Setiari Jmh; Putu Ratna Windusara Putri (Yayasan Nusantara Hasana Berdikari, 2024)
Tourism investment has become one of the main drivers of economic growth in the Nusa Dua area, Bali. The development of tourism facilities such as hotels, restaurants, shopping centers, and supporting infrastructure has created new economic opportunities for surrounding village communities. This study aims to analyze the effect of tourism investment on changes in the livelihood structure of village communities around Nusa Dua. A quantitative approach with a survey method was employed involving residents living in villages surrounding the Nusa Dua tourism area. Data were analyzed using descriptive and inferential techniques to identify occupational shifts before and after tourism investment expansion. The findings indicate that tourism investment significantly influences the transformation of livelihoods from primary sectors, particularly agriculture and fisheries, to tourism-related service sectors. This transformation has increased household income and employment opportunities; however, it has also generated challenges such as the reduction of productive land, economic dependency on tourism, and socio-cultural changes. Therefore, sustainable and community-based tourism development policies are required to ensure that economic benefits are distributed equitably while maintaining social and environmental sustainability.